Beckwith-Wiedemann syndrome: a demonstration of the mechanisms responsible for the excess of transmitting females. Issue 4 (April 1992) - Moutou, C; Junien, C; Henry, I; Bonaïti-Pellié, C
Abstract : Beckwith-Wiedemann syndrome (BWS) is often associated with embryonal tumours (nephroblastoma, adrenocortical carcinoma, hepatoblastoma, and rhabdomyosarcoma). Several pedigrees have been reported strongly suggesting autosomal dominant inheritance and an excess of transmitting females was noticed in these families. We confirmed this excess using 19 published pedigrees and showed that this excess was for two reasons: first, reduced fecundity in affected males compared to females in a ratio of 1:4.6, and, second, a smaller risk of being affected in a ratio of 1:3 for subjects having inherited the gene from their father. These latter findings suggest genomic imprinting. Furthermore, considering these results together with other observations, such as the parental origin of the 15p15.5 duplication and the existence of uniparental disomy in some sporadic cases, we propose that overgrowth in BWS patients and malignant proliferation in associated tumours reflect an imbalance between paternal and maternal alleles.